Incubadora de empresa madeireira um estudo de caso em Telêmaco Borba - Machado, Valtimi (2013)
This work was to discuss the issue in public management municipal entrepreneurship, exploring the possibility of creating an incubator Lumber Company for construction of ecological house in Telêmaco Borba has on its surrounding municipalities of Tibagy, Reserve, Gale, and Ortigueira Imbaú in which part of this, micro region. Information was raised on the population, land use, employment and sustainability. Information from literature searches, conducted by Institute research as IPARDES, SEBRAE, municipalities journals. You can verify that this region is the sixth largest timber hub of Paraná and has the largest manufactures pulp and paper in Latin America that Industry Klabin do Paraná in which has a large reserve forest of pine and eucalyptus and keeps on his farm large area of native forests.